PEMANFAATAN LIMBAH PABRIK KELAPA SAWIT SEBAGAI MATERIAL TEKNIK - Tarkono Tarkono; Hadi Ali (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Palm oil mill issuesbyproducts in the form of 0.70 tons of cubic meters of fiber, 0.35 tons of cubic meters of shell,and 1.1 tons of cubic meters of oil palm empty fruit bunches palm (EFBP) to yield 1 ton cubic meters of crude palm oil.The fiber content consisted in the EFB is a source of fiber for a variety of industries such as manufacturing of composites, fillers for thermo-plastic, paper-making and sound insulation as well as soil erosion control.Manufacturing of a natural fiber reinforced cement board is an effort to reduce the use of synthetic fibers and asbestos fibers which cause side effects for its users.So this research is one of the breakthroughs to obtain new materials as substituteto asbestos fibers. This research used portland cement, marble powder, CaCO3 and EFBP fiber as reinforcement.EFBP fibers were arranged randomly in the form of short fibers. Percentage of the mixture of 16%, 12% marble powder, and portland cement was varied with a percentage of 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15% and the volume percentage of CaCO3 inverse of the percentage of portland cement. The results showed that the characteristics of fibrous EFBP cementboard in the optimum condition to produce value of tensile strength of 1.96 MPa, flexural strength of 2.61 MPa, compressive strength of 14.35 MPa, density (ρ) of 1519 kg/cm3, water absorption of 24.28 and flame propagation velocity between 54.4 to 61.5 FS.By the standard of JIS A 5417-1992 that the requirements of density in the construction of cement board is of 0.8 g/ cm3, so that the material is appropriate to be applied.Its thermal conductivity lower than fibrous congseted asbestos cement board λ = 0.576 kcal/mhoC, meaning that the cement board is worthy applied as a ceiling of the house. Keywords:EFPB, fiber, cement board, engineering material